The impact of social media usage, social support, peer influence, and social identity on the self-concept of youths in Enugu East Local Government Council, Nigeria - Bibian, Omeye Ebube; Ma’rof, Aini Azeqa (Human Resource Management Academic Research Society, 2024)
This study examines the influence of social media usage, social support, peer influence, and social identity on self-concept among youths in Enugu East Local Government Council, Nigeria. Using a quantitative approach with 404 participants, Pearson correlation and multiple regression analyses were conducted. Results indicate that social support was the strongest predictor of positive self-concept, followed by social identity, peer influence, and social media usage. These findings highlight the pivotal role of social support in enhancing self-concept, alongside the significant contributions of social identity and peer dynamics in shaping self- perceptions. Notably, social media usage, though a weaker predictor, reflects the influence of global digital engagement trends on youth identity development in a Nigerian context. By integrating these insights, this research contributes to a broader understanding of self- concept formation, offering implications for programs aimed at fostering positive identity development in digitally interconnected, culturally grounded youth communities.